The Influence of Artificial Intelligence in Chatbots and Website Personalization on Customer Engagement with User Experience as an Intervening Variable - Osly Usman; Sastrodiningrat, Rafilino (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study examines the influence of Artificial Intelligence (AI) in chatbots and website personalization on customer engagement, with user experience serving as a mediating variable. The integration of AI in digital platforms has revolutionized how businesses interact with their customers by providing more efficient and customized services. AI-powered chatbots enable instant communication, addressing customer inquiries and issues promptly, while website personalization tailors content, design, and recommendations to individual user preferences, enhancing relevance and satisfaction. Adopting a quantitative research approach, this study evaluates the direct effects of these AI-driven tools on customer engagement and investigates the mediating role of user experience. The results reveal that AI-enabled chatbots and personalized websites significantly contribute to improved customer engagement. Additionally, user experience acts as a critical intermediary, amplifying the effectiveness of these technologies in fostering deeper customer connections. The study underscores the importance of seamless and intuitive user experiences in maximizing the benefits of AI-based innovations. These findings provide valuable insights for businesses looking to leverage AI to enhance their digital strategies, improve customer satisfaction, and drive engagement. This research contributes to the growing body of knowledge on AI in digital marketing and its implications for building stronger customer relationships.